DEFAULT ON DEBT COLLECTOR SERVICE REWARDS IN IJĀRAH 'ALĀ AL-'AMĀL CONTRACT: (Analysis Of Decision Number 324/Pdt.G/2024/MS. Bna) - Faris Ghifary; Muhammad Syuib (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2026)
This study analyzes the legal considerations of judges in Decision Number 324/Pdt.G/2024/MS. Bna concerning a dispute over the non-performance of service fee payments between Bank Aceh Syariah and a debt collection company. The research employs a normative juridical method with statutory, case, and conceptual approaches. The analysis is conducted based on the Indonesian Civil Code, the Compilation of Sharia Economic Law, DSN-MUI fatwas, and the concept of ijarah 'ala al-'amal in Islamic jurisprudence (fiqh muamalah). The main findings indicate that the judges appropriately qualified the defendant's actions as a breach of contract; however, the legal reasoning remains predominantly grounded in civil law and has not fully utilized the ijarah 'ala al-'amal contract as a substantive analytical framework. This study emphasizes the importance of coherently integrating positive law and fiqh muamalah in the resolution of Sharia economic disputes.